How Do I Confirm that a New Mutation is Pathogenic?. Issue 2 (23rd March 2018) - Trinh, Joanne; Tadic, Vera; Klein, Christine
Abstract: View Supplementary Video 1 Whole exome, genome sequencing, and other massive parallel next generation sequencing technologies have increasingly been used as a clinical diagnostic tool in recent years. Although sequencing technologies are becoming more affordable and widely used, the interpretation of variants from these large datasets at the level of personalized medicine is not clear‐cut. For example, many rare missense variants identified may or may not have an impact on gene function and can be problematic to interpret in a clinical setting. Thus, there is a need for a systematic approach to applying, reporting, and evaluating variants identified. One important aspect is to determine the pathogenicity of a variant based on scientific literature. This tutorial is meant to serve as an introduction to scoring pathogenicity of variants, enabling movement disorder specialists to familiarize themselves with online tools to independently determine pathogenicity of variants identified in genetic testing reports. Abstract : View Supplementary Video 1